1991
DOI: 10.1073/pnas.88.4.1398
|View full text |Cite|
|
Sign up to set email alerts
|

Pollen-mediated introgression and hybrid speciation in Louisiana irises.

Abstract: Populations of the "Louisiana iris" species Iris fulva, I. hexagona, and I. nelsonii were examined genetically to test for interspecific gene flow between I. fulva and I. hexagona, for pollen- versus seed-mediated introgression between these species, and for the presumed hybrid origin of I. nelsonii. Genetic markers were identified by using both a polymerase chain reaction-like method that allows the identification of random, nuclear markers and standard polymerase chain reaction experiments involving specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
178
1
3

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 290 publications
(190 citation statements)
references
References 12 publications
8
178
1
3
Order By: Relevance
“…The rbcL-ORF106 region was difficult to amplify for many species using the primers described in Arnold et al (1991), and was not successfully amplified for 27 species. Amplification problems were apparently due to the ORF106 primer, which appears to be part of variable spacer region, rather than a coding region as originally thought.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rbcL-ORF106 region was difficult to amplify for many species using the primers described in Arnold et al (1991), and was not successfully amplified for 27 species. Amplification problems were apparently due to the ORF106 primer, which appears to be part of variable spacer region, rather than a coding region as originally thought.…”
Section: Methodsmentioning
confidence: 99%
“…Five regions of the chloroplast genome located within the large single copy region were amplified via PCR: trnT-trnF (Taberlet et al 1991), rbcL-ORF106 (Arnold et al 1991), trnH-trnK (Demesure et al 1995), trnF-trnV, andtrnV-rbcL (Dumoulin-Lapègue et al 1997). The approximate length of each region in Poa is as follows: trnT-trnF, ϳ1800-1850 base pairs (bp); trnF-trnV, ϳ3100-3280 bp; trnV-rbcL, ϳ3900-4000 bp; rbcL-ORF106, ϳ2250-2550 bp; and trnH-trnK, ϳ1950-2000 bp.…”
Section: Methodsmentioning
confidence: 99%
“…The area of geograph-ical overlap between these three species occurs in southern Louisiana and numerous cases of natural hybridization have been reported from this region (Viosca, 1935;Riley, 1938;Anderson, 1949;Randolph eta!. 1967;Bennett & Grace, 1989;Arnold et a!., 1 990a, b;1991). Recent studies of this species complex have determined the distribution of nuclear, genetic markers and have led to the inference of both sympatric and allopatric introgression (Arnold et a!., 1 990a, b;1991).…”
mentioning
confidence: 99%
“…1967;Bennett & Grace, 1989;Arnold et a!., 1 990a, b;1991). Recent studies of this species complex have determined the distribution of nuclear, genetic markers and have led to the inference of both sympatric and allopatric introgression (Arnold et a!., 1 990a, b;1991). An initial study of chloroplast DNA (cpDNA) markers for I. fu!va and I. hexagona suggested that introgression between these two species was a result of pollen being transferred between allopatric populations of the taxa rather than seed dispersal followed by pollen transfer (Arnold et a!., 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation